Mortality dynamics in an old-growth stand of beech (Fagus sylvatica) in Southern Sweden - Fuentes Perivancich, Mauricio Ivan (2010)
Mortality patterns were assessed in an old growth beech stand in southern Sweden. A previous inventory of 1200 trees in 1996 was used as a base for an inventory in 2006. Mann-Whitney U test was used to compare statistical distribution between living and dead trees of those inventoried in 2006. Dendrochronological reconstruction was applied for assessment of the temporal patterns of mortality. The mortality rate was 18% in ten years, affecting mainly larger diameter classes >40cm dbh. During the study period, 6.9 % of the total amounts of living trees became high stumps, from which 45% subsequently died. In understory trees, growth reactions and scars related to tree falls and canopy damage increased by over 80 % between the 1970’s and the 1990’s, suggesting an increasing disturbance rate over this period. The causes of death could not be attributed to disturbances by themselves, but rather to a combination of fungal infection (mainly Fomes fomentarius) and wind in most cases. The mortality level found in this beech population is rather high compared to other studies in European deciduous forest. Since the age of the stand is near the reported maximum of the species, mortality is likely to be high in the future. Damaged beech trees that survive a long time (over ten years) provide unique substrate for species assemblages, constituting a desirable feature for conservation.